PENGARUH KUALITAS PRODUK DAN STORE ATMOSPHERE TERHADAP KEPUASAN PELANGGAN DI RUMAH MAKAN WOK TEK KUTA BADUNG - Kadek Medha Prayascita; Ni Made Suci (Universitas Pendidikan Ganesha, 2022)
This study aims to examine the effect of product quality and store atmosphere either simultaneously or partially on customer satisfaction at WOK TEK Restaurant Kuta Badung. The research design used is causal quantitative research. Determination of the sample in the study using non-probability sampling and purposive sampling techniques. The number of samples used is 150 respondents. The instrument used in data collection is a questionnaire and the data analysis technique used is multiple linear regression analysis. The results of this study are: (1) product quality has a positive and significant effect on customer satisfaction at WOK TEK Kuta Badung Restaurant. (2) store atmosphere has a positive and significant effect on customer satisfaction at WOK TEK Kuta Badung Restaurant. (3) Product quality and store atmosphere have a significant effect on customer satisfaction at WOK TEK Kuta Badung Restaurant.